Quản trị nhân tài và giữ chân nhân viên: Vai trò điều tiết của hợp đồng tâm lý - Đoàn Viết , Nhân; Phan Quốc , Tấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Talent management is regarded as a strategic lever for enhancing employee retention in the construction industry, where labor market volatility is high. This study examines the impact of talent management on employee retention in construction enterprises in Ho Chi Minh City, while also investigating the mediating roles of employer branding and perceived job insecurity, with particular emphasis on the moderating role of the psychological contract. Survey data from 355 employees were analyzed using the PLS-SEM approach. The results indicate that talent management does not exert a direct positive effect on employee retention; however, it has significant indirect effects through two mechanisms: (i) strengthening employer branding, thereby increasing employees’ tendency to stay; and (ii) reducing perceived job insecurity, thereby improving retention. Among these mechanisms, employer branding plays a prominent mediating role and almost fully transmits the effect of talent management on employee retention. Notably, the psychological contract strengthens the effectiveness of talent management in enhancing employer branding, reducing job insecurity, and improving employee retention, suggesting that talent management practices yield favorable outcomes only when organizational commitments are implemented in a consistent and credible manner